1A If Zfxy With Xet Y T23T2 Upsidedown Delta

Question

1a) If z=f(x,y), with x=e^t, y= t^2+3t+2, upsidedown delta f=(2xy^2-y, 2x^2y-x) find z’(t) at t=0 b) parametrize surface (y-2)^2+(z-3)^2=4 Please answer asap for thumbs up, thanks

1a)
If z=f(x,y), with x=e^t, y= t^2+3t+2, upsidedown delta f=(2xy^2-y,
2x^2y-x) find z’(t) at t=0
b)
parametrize surface (y-2)^2+(z-3)^2=4
Please answer asap for thumbs up, thanks

Solutions

Expert Solution


Submit Your Answer

[contact-form-7 id=”5″ html_class=”cf7_custom_style_1″ title=”Answer Question”]